Interaksi Dinamis Antara Motivasi Siswa Dan Kinerja Guru Di Mts Al Mukhtariyah 1 Cihalimun - Devi Nutriani, Santi; Fauziya, Fizi (Lembaga Pengembangan Kinerja Dosen, 2025)
This reserch aims to analyze the student motivation and teacher performance at Mts Almukhtariyah 1 Cihalimun. The method used was a descriptive qualitative approch with a survey invloving one teacher and two students. The data colletion tecnique used was by means of interviews, observation and in-dept documentation of informationts. The research results show thats student’learning motivation at Mts Almukhtariyah 1 Cihalimun is very good so that teachers play an important role in their enthusiasm for learning. As an educational workforce, good teacher performance can increase student motivaton, thereby improving learning outcomes and academic achievement. In this reserch, teacher performance at Mts Almukhthariyah 1 Cihalimun was assessed by their ability to convey material and use of varied methods.